EFEKTIVITAS KAWASAN HUNIAN SEMENTARA SEBAGAI MEDIA PEMULIHAN PENGUNGSI PASCA BENCANA MERAPI 2010 STUDI KASUS PADA KAWASAN HUNIAN SEMENTARA PLOSOKEREP, GONDANGPUSUNG, BANJARSARI, DAN GONDANGLEGI - , FARAH SANTY AFFISA, Prof. Ir. A. Djunaedi, MUP, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Disaster management is a complex and sensitive issue for the disaster victims in the period of transition and post-disaster vulnerability. The construction of temporary shelters intended as an effort to bridge transitional period between the phases of relief and reconstruction is completed , hopefully it is able to mitigate the suffering of the victims of Merapi Eruption 2010. In fact, there are a lot of problems faced by resident such as comfort, refusal, being left stranded by the resident. The existence of a standard UNHCR expected to be a reference in making shelters is not widely implemented thoroughly by the organizers, so many emerging standard variations on each region. On the other hand the government generally do not have standardization and guidelines for top disaster management. Based on the number of arising problems, then paradigm was emerged that temporary shelter of Merapi 2010 was not the best solution in the recovery management of postdisaster. This study is intended to look at the effectiveness of temporary-shelter region as recovery place of merapi post-disaster 2010. The criteria for comparison of the implementation of UNHCR to the selected temporary-shelter region such as Region Plosokerep, Banjarsari, Gondangpusung, and ACT., resident satisfaction level and their contributing factors as well as resident-adaptation embodiment can be used as a counterweight in the determination of standardization in the manufacture of future disaster recovery program . The approach to achieve these goals is comparative-case-study approach with qualitative methods. The information required in analyzing the information target needed in analyzing existing targets is through the process of deep interview to the third resident of temporary-shelter region, particularly resident who is more competent in conveying the necessary information. In addition to the interview information can be obtained by field observations in the form of image documentation. The results of this study showed that only 87 % of reference of UNHCR standard was actually applied in reference to the process of implementation of building temporary shelters 2010, particularly in the area of government program , while in some non-government program such as the ACT was only 62 % used . The level of resident acceptance of temporary shelter of Merapi 2010 only reached 67 %. The small percentage of satisfaction was much influenced by the quality of temporary shelter from the bureaucracy that cause delay in workmanship, quality housing, participation, and most importantly the confidence of the residents to the economic program and certainty of future livelihood in addition to background factors such as the characteristics of the resident who tends to be conventional and sticking with traditional values as well as high dependence on agriculture and animal husbandry became origin livelihood. Most embodiment of adaptation was regional changes linked to economic activity, and the change of room to be comfortable. hange made by the The c residents cannot be separated from the relationship between living duration and the following need. The result of the analysis of residentâs response and hope resulted linkage " duration" transition between the emergency phase and reconstruction phase in need and form of temporary-shelter region focusing on recovery of the victim lives. The resident response toward the duration and the form of the region resulted in three criteria of shelter-region selection strategy which wass described as an inverted pyramid that illustrated the peak of the intensive management and complexity of a region such as a) . 1-2 months or safe phase , b ) . 2-6 months or comfortable phases and c ) . 6-18 months or Livelihood phase. Based on the parameter of duration and the need from the three samples of regional group, it could be concluded that the three groups was not effective as a solution to refugee management 2010 , but among the three groups, group 2 is one of the groups approached the parameter criteria assessed in case there will be an improvement ranging from the duration, speed, and economic activity.